Facial Biometrics of Yorubas of Nigeria Using Akinlolu‑Raji Image‑processing Algorithm - Akinlolu, Adelaja (Journal of Medical Sciences, 2016)
Background: Forensic anthropology deals with the establishment of human identity using genetics, biometrics, and face recognition technology. This study aims to compute facial biometrics of Yorubas of Osun State of Nigeria using a novel Akinlolu‑Raji image‑processing algorithm. Materials and Methods: Three hundred Yorubas of Osun State (150 males and 150 females, aged 15–33 years) were selected as subjects for the study with informed consents and when established as Yorubas by parents and grandparents. Height, body weight, and facial biometrics (evaluated on three‑dimensional [3D] facial photographs) were measured on all subjects. The novel Akinlolu‑Raji image‑processing algorithm for forensic face recognition was developed using the modified row method of computer programming. Facial width, total face height, short forehead height, long forehead height, upper face height, nasal bridge length, nose height, morphological face height, and lower face height computed from readings of the Akinlolu‑Raji image‑processing algorithm were analyzed using z‑test (P ≤ 0.05) of 2010 Microsoft Excel statistical software. Results: Statistical analyzes of facial measurements showed nonsignificant higher mean values (P ＞ 0.05) in Yoruba males compared to females. Yoruba males and females have the leptoprosopic face type based on classifications of face types from facial indices. Conclusions: Akinlolu‑Raji image‑processing algorithm can be employed for computing anthropometric, forensic, diagnostic, or any other measurements on 2D and 3D images, and data computed from its readings can be converted to actual or life sizes as obtained in 1D measurements. Furthermore, Yoruba males and females have the leptoprosopic face type.